An exploration of stakeholder perceptions to inform the development of an evidence-based classification system in para dressage - St. George, L.; Thetford, C.; Clayton H. M.; Hobbs, S. J. (Journal of Sports Sciences, 2022)
In dressage, horse-rider combinations must demonstrate harmony whilst performing a test of gaits and movements, scored by judge(s) using predetermined criteria. The para dressage governing body is working towards compliance with the International Paralympic Committee`s mandate for evidence-based classification, which requires a comprehensive understanding of key performance determinants. This study aimed to explore stakeholder perceptions surrounding the key determinants of, and impact of impairment on, para dressage performance. Semi-structured interviews with 30 para dressage stakeholders (athletes, classifiers, judges, coach) were analysed using the Framework method. Themes relating to the equine and human athlete were associated with overall dressage performance and discussed within the context of impairment and horse-rider partnership. Key performance determinants were summarised as the athlete`s ability to maintain dynamic postural control for absorbing the horse`s movement and coordinating leg, hand, and seat aids, which directly influence the horse`s quality and accuracy of movements during dressage. Thus, muscular coordination, joint mobility that influences rider posture, and personality traits that influence the horse-rider partnership were considered performance determinants. These themes will inform the development of an evidence-based classification system, through the establishment of standardised, sport-specific performance measures for assessing the relationship between impairment and activity limitation in para dressage.